Analysis of flexible supported industrial robot on terminal accuracy. (13th August 2018) - Wang, Liping; Chen, Lian; Shao, Zhufeng; Guan, Liwen; Du, Li
To meet comprehensive performance requirements of large workspace, lightweight, and low energy consumption, and flexible supported industrial robots emerge, which are usually composed of a six-degrees-of-rotational-freedom (6R) industrial robot and a flexible support. Flexible support greatly expands the motion range of the attached industrial robot. Flexible supported industrial robots have been adopted in surface coating of large structures such as aircrafts and rockets. However, the rigid–flexible coupling exists in these robot systems. When the industrial robot moves, the reaction force and torque of the robot disturb the flexible support and introduce vibration, which may result in the deterioration of the system's terminal accuracy. This study focuses on both the robot body accuracy and system vibration suppression to improve the terminal accuracy of the flexible supported industrial robot. Firstly, based on kinematics analysis, accuracy of the industrial robot is investigated with the local conditioning index. Then, reaction force and torque ellipsoids are proposed with the deduced dynamic model to evaluate disturbances that the industrial robot applies to the flexible support. Considering these two aspects, the high-quality workspace of the flexible supported industrial robot is established. Numerical simulations show that reaction force and torque are effectively limited in the high-quality workspace, which greatly reduce the vibration energy and improve the terminal accuracy of the system.